Thermo-sensitive nano-cellulose-based hydrogel with semi-interpenetrating network structure and preparation method of thermo-sensitive nano-cellulose-based hydrogel
By constructing a semi-interpenetrating network structure of nanocellulose-based hydrogels, the problems of slow temperature response and poor biocompatibility of traditional hydrogels are solved, achieving rapid temperature response and efficient antibacterial effect, suitable for wound dressings, and promoting tissue regeneration and healing.
Patent Information
- Application Number
- CN202511346803.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-19
- Publication Date
- 2025-12-05
AI Technical Summary
Existing wound dressing hydrogels have slow temperature response and poor biocompatibility, making it difficult to meet the needs for rapid response and efficient antibacterial properties.
A nanocellulose-based hydrogel with a semi-interpenetrating network structure is formed by physical and chemical crosslinking of aldehyde-modified nanocellulose with water-soluble polysaccharide derivatives and thermosensitive monomers, resulting in a hydrogel with rapid temperature response and high antibacterial efficiency. A second network is formed by crosslinking aldehyde-modified nanocellulose with carboxymethyl chitosan using the Schiff base, and a first network is formed by free radical covalent linkage of N-isopropylacrylamide.
It achieves a reversible temperature response of hydrogel within 300 seconds, has highly efficient antibacterial properties, and has an inhibition rate of 99.95% against Staphylococcus aureus and Escherichia coli. It provides painless adhesion and non-invasive replacement, maintains a moist wound environment, and promotes tissue regeneration.
Smart Images

Figure CN121059879A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of hydrogel, in particular to a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel and a preparation method thereof. BACKGROUND
[0002] Skin damage not only triggers a series of adverse physiological reactions, but also significantly increases the risk of infection. Traditional dressings such as gauze, adhesive tape and bandage materials, although they can effectively prevent wound contamination, have the problems of insufficient antibacterial properties and poor air permeability, and are accompanied by poor adhesion, peeling and high susceptibility to infection.
[0003] Hydrogel-type wound dressings have attracted much attention due to their ability to maintain a moist wound environment, reduce the risk of infection, and relieve wound pain, and have been widely recognized in clinical applications. However, ordinary hydrogels can only passively absorb water and swell, while intelligent hydrogels can sense changes in the external environment (such as temperature, ionic strength, pH, osmotic pressure, etc.) and undergo a sudden volume response. With the reversible changes in external stimuli, the sudden change of hydrogel is also reversible. Therefore, the application of intelligent hydrogels in the field of wound dressings has broad application prospects.
[0004] Nanocellulose not only has excellent biodegradability, renewability and easy chemical modification characteristics, but also exhibits extremely high tensile strength, high specific surface area and low density, which are crucial for the development of cellulose-based hydrogel materials. The addition of N-isopropyl acrylamide can impart excellent temperature response performance, and the use of reversible conformational changes of polymer molecules under specific temperature stimuli enables an intelligent phase transition process from a liquid precursor to a three-dimensional gel network. Although temperature-sensitive hydrogels have shown certain therapeutic effects as wound dressings, they still face key problems such as slow temperature response and poor biocompatibility.
[0005] After searching, Chinese Patent Publication No. CN222075415U discloses a wound dressing based on poly-N-isopropyl acrylamide hydrogel microspheres, which designs a temperature and humidity sensor to realize the function of timed drug release, but does not discuss its biocompatibility; Chinese Patent Publication No. CN115975122A discloses a preparation method of temperature-sensitive interpenetrating network hydrogel, which prepares a hydrogel that can be used for temperature-sensitive drug release, showing its effect of using temperature sensitivity for drug release, but does not discuss the actual use effect of the hydrogel dressing. SUMMARY
[0006] In view of the deficiencies of the prior art, the present application provides a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel and a preparation method thereof, which solves the problems of slow temperature response and poor biocompatibility of existing wound dressing hydrogels.
[0007] To achieve the above object, the present application is implemented by the following technical scheme: a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel, which is prepared by physical cross-linking and chemical cross-linking of water, aldehyde-modified nanocellulose, water-soluble polysaccharide derivative and temperature-sensitive monomer; The aldehyde-modified nanocellulose is prepared by aldehyde modification treatment of nanocellulose extracted from cotton and hemp plants using sodium periodate; The water-soluble polysaccharide derivative is one or several of carboxymethyl chitosan or quaternary ammonium salt chitosan; The temperature-sensitive monomer is one or several of N-isopropyl acrylamide or poloxamer; The aldehyde-modified nanocellulose and the temperature-sensitive monomer are covalently connected by free radicals to form a first network; The aldehyde-modified nanocellulose and the water-soluble polysaccharide derivative form an imine bond to form a second network.
[0008] Preferably, the nanocellulose extracted from cotton and hemp plants is one or both of nanocellulose crystals and nanocellulose fibers.
[0009] Preferably, the water-soluble polysaccharide derivative is carboxymethyl chitosan.
[0010] Preferably, a preparation method of a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel comprises the following steps: Step one: mix the nanocellulose solution with the sodium periodate solution, adjust the pH of the mixed system to 4-5 using PBS at room temperature 20-25℃, and stir under the condition of 100-200r / min for 12h-24h to obtain a first solution; wherein the weight ratio of sodium periodate to nanocellulose is 1.19-3.66:1; Step two: add ethylene glycol to the first solution, the molar ratio of ethylene glycol to sodium periodate in step one is 1:1, and stir under the condition of 20℃-25℃ and 100-200r / min for 1h-2h to obtain a second solution; Step three: place the second solution in a dialysis bag with a molecular weight cut-off of 4500Da, dialyze with deionized water for 3-5 days, freeze-dry the solution after dialysis for 3 days, add deionized water to the dried product and ultrasonic disperse for 24h to obtain a third solution with a mass fraction of 1.0wt%; Step four: add temperature-sensitive monomer and first initiator to the third solution, stir under the condition of 20℃-25℃ and 100-200r / min for 1h-2h under nitrogen protection to obtain a fourth solution; Step five: the second initiator is added into the fourth solution, and the reaction is stirred at 20-25 DEG C and 100-200 r / min for 10-30 min to obtain a fifth solution; Step six: the fifth solution is loaded into a dialysis bag with a molecular weight cut-off of 4500 Da, and dialysis is performed with deionized water for 1-3 days to obtain a sixth solution; Step seven: a water-soluble polysaccharide derivative is added into deionized water, and the use amount ratio of the water-soluble polysaccharide derivative to deionized water is 2.25g:50ml, and the reaction is stirred at 20-60 DEG C and 100-200 r / min for 12-24h to obtain a seventh solution; Step eight: the sixth solution is added into the seventh solution, and the volume ratio of the seventh solution to the sixth solution is 1:1-2, and the reaction is stirred at 10-25 DEG C and 10-100 r / min for 5-10 min to complete physical crosslinking and chemical crosslinking, thereby obtaining the semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel.
[0011] Preferably, in step one, the nanocellulose is nanocellulose fiber, the stirring reaction temperature is 25 DEG C, and the stirring reaction time is 24h.
[0012] Preferably, in step four, the temperature-sensitive monomer is N-isopropyl acrylamide, the first initiator is N,N,N',N'-tetramethyl ethylenediamine, the reaction temperature is 25 DEG C, and the reaction time is 1h.
[0013] Preferably, in step five, the second initiator is ammonium persulfate, the reaction temperature is 25 DEG C, and the reaction time is 10 min.
[0014] Preferably, in step seven, the water-soluble polysaccharide derivative is carboxymethyl chitosan, the stirring temperature is 25 DEG C, and the stirring time is 24h.
[0015] Preferably, in step eight, the stirring temperature is 15 DEG C, and the stirring time is 5 min.
[0016] The present application provides a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel and a preparation method thereof. The present application has the following beneficial effects: The aldehyde group nanocellulose is used as a gel skeleton, a poly(N-isopropyl acrylamide) segment is grafted onto the aldehyde group nanocellulose through free radical graft copolymerization, temperature stimulus response performance is given to the composite hydrogel to form a first network of the hydrogel, and the aldehyde group nanocellulose and Schiff base crosslinking of carboxymethyl chitosan form a second network of the hydrogel, so that a temperature-responsive hydrogel with a semi-interpenetrating network structure is successfully constructed. The aldehyde group nanocellulose provides a large number of hydrogen bonds for the hydrogel, can effectively absorb wound exudate and lock water, and maintains a moist microenvironment; and the uniform three-dimensional porous structure of the hydrogel provides a continuous pore size for water molecules to enter and exit, thereby ensuring the drying of the wound surface and avoiding excessive immersion. Meanwhile, the hydrogel has fast and mild temperature responsiveness, can complete the solution-gel reversible conformational transition within 300s, can be seamlessly fitted with the wound in a liquid state, is converted into a gel at the skin temperature to protect the wound, and only needs to be locally cooled to be converted into a liquid state when dressing, so that the effect of painless sticking and non-invasive replacement is realized; the hydrogel has good antibacterial property, and the inhibition rates of staphylococcus aureus and escherichia coli are both 99.95%.
[0017] The nanocellulose of the application is derived from a natural structural material, has excellent biocompatibility and biodegradability, can provide a good growth microenvironment for cells, and effectively supports the process of tissue regeneration and repair. Meanwhile, the natural polymer derivative carboxymethyl chitosan is used as a core antibacterial component, a dual sterilization mechanism of destroying the integrity of bacterial cell membranes and inhibiting the activity of key enzymes is used, and high-efficiency antibacterial effect is synergistically achieved. For common wound infection strains such as staphylococcus aureus and escherichia coli, the inhibition rates are all above 99%, which significantly exceeds the inhibition level of 80%-90% of traditional dressings, can rapidly inhibit pathogenic bacteria colonization and reproduction, effectively block the formation of biofilms and the spread of infection, and provide a clean and safe microenvironment for wound healing.
[0018] The application constructs a semi-crosslinked interpenetrating network structure nanocellulose hydrogel with reversible temperature response characteristics by selecting N-isopropyl acrylamide and nanocellulose for free radical graft copolymerization reaction, and further using the Schiff base reaction between nanocellulose and carboxymethyl chitosan. The volume phase transition temperature of the hydrogel is about 34 DEG C, close to the normal temperature of human skin, so that the hydrogel can be rapidly converted from a solution state to a gel state in a very short time after contacting the skin, can be seamlessly fitted with the wound in a liquid state, is converted into a gel at the skin temperature, realizes rapid gelation and good adhesion, protects the wound, and only needs to be locally cooled to be converted into a liquid state when dressing, so that the effect of painless sticking and non-invasive replacement is realized.
[0019] The application successfully constructs a semi-interpenetrating network hydrogel with complex structure by taking nanocellulose, N-isopropyl acrylamide and carboxymethyl chitosan as raw materials, which has a highly uniform and stable three-dimensional porous structure with a pore size distribution of 50-100 mu m, and a dense and smooth pore wall, thereby providing a channel for water molecules to enter and exit, ensuring the drying of the wound surface and avoiding excessive immersion. The hydrogel exhibits excellent water absorption in the gel state, with a water absorption rate of up to 1415.36% within 8 hours. This property enables the hydrogel to efficiently and continuously absorb a large amount of wound exudate, effectively managing wound exudation while avoiding surrounding skin immersion, locking the absorbed liquid in the gel network, maintaining an ideal and stable moist environment for wound healing, thereby accelerating the growth of granulation tissue and epithelial cell migration. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 SEM image of the cross section of the hydrogel dressing prepared in Example One of the application; Figure 2 SEM image of the cross section of the hydrogel dressing prepared in Example Two of the application; Figure 3 SEM image of the cross section of the hydrogel dressing prepared in Example Three of the application; Figure 4 SEM image of the cross section of the hydrogel dressing prepared in Example Four of the application; Figure 5 SEM image of the cross section of the hydrogel dressing prepared in Example Five of the application; Figure 6 SEM image of the cross section of the hydrogel dressing prepared in Example Six of the application; Figure 7 SEM image of the cross section of the hydrogel dressing prepared in Example Seven of the application; Figure 8 Comparison chart of temperature response performance of the hydrogels prepared in Examples One, Two, Four to Seven of the application; Figure 9 Swelling rate chart of the hydrogels prepared in Examples Three to Seven of the application; Figure 10 Microscopic image of the antibacterial effect of the hydrogels prepared in Examples One and Four to Seven of the application on Staphylococcus aureus and Escherichia coli, wherein Figure 10 A is the agar plate culture result chart of different hydrogels, Figure 10 B is a column chart of the antibacterial rate of different hydrogels on Staphylococcus aureus, Figure 10 C is a column chart of the antibacterial rate of different hydrogels on Escherichia coli. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0022] A semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel is prepared by physical cross-linking and chemical cross-linking of water aldehyde-modified nanocellulose, water-soluble polysaccharide derivatives and temperature-sensitive monomers. The aldehyde-modified nanocellulose is prepared from nanocellulose extracted from cotton and hemp plants by aldehyde treatment with sodium periodate. The water-soluble polysaccharide derivative is one or several of carboxymethyl chitosan or quaternary ammonium salt chitosan. The temperature-sensitive monomer is one or several of N-isopropyl acrylamide or poloxamer.
[0023] Nanocellulose, carboxymethyl chitosan material and N-isopropyl acrylamide material form hydrogen bonds, and nanocellulose and carboxymethyl chitosan form imine bonds, so as to prepare a nanocellulose-based temperature response wound dressing hydrogel by physical and chemical cross-linking, which is suitable for wound dressing.
[0024] A preparation method of a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel, comprising the following steps: Step one: mix a nanocellulose solution with a sodium periodate solution, adjust the pH of the mixed system to 5 by PBS at room temperature 20-25 DEG C, and stir under the condition of 150 r / min for 24 h to obtain a first solution; wherein the weight ratio of sodium periodate to nanocellulose is 2.0:1; Step two: add ethylene glycol to the first solution, the molar ratio of ethylene glycol to sodium periodate in step one is 1:1, and stir under the condition of 25 DEG C, 200 r / min for 2 h to obtain a second solution; Step three: pack the second solution into a dialysis bag with a molecular weight cut-off of 4500 Da, dialyze with deionized water for 5 days, freeze dry the solution for 3 days after dialysis is completed, add deionized water to the dried product and ultrasonic dispersion for 24 h to obtain a third solution with a mass fraction of 1.0 wt%; Step four: add a temperature-sensitive monomer and a first initiator to the third solution, and stir under the condition of 25 DEG C, 200 r / min for 2 h under nitrogen protection to obtain a fourth solution; Step five: add a second initiator to the fourth solution, and stir under the condition of 25 DEG C, 200 r / min for 30 min to obtain a fifth solution; Step six: the fifth solution is loaded into a dialysis bag with a molecular weight cut-off of 4500 Da, and dialyzed with deionized water for 3 days to obtain a sixth solution; Step seven: a water-soluble polysaccharide derivative is added to deionized water, and the use amount ratio of the water-soluble polysaccharide derivative to deionized water is 2.25 g:50 ml, and the mixture is stirred at 60°C and 200 r / min for 24 h to obtain a seventh solution; Step eight: the sixth solution is added to the seventh solution, and the volume ratio of the seventh solution to the sixth solution is 1:2, and the mixture is stirred at 25°C and 100 r / min for 10 min to complete the physical crosslinking and chemical crosslinking, thereby obtaining the semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel. Embodiment
[0025] The embodiment of the present application provides a preparation method of a temperature-sensitive hydrogel, which comprises the following steps: (1) N-isopropyl acrylamide is dissolved in deionized water to prepare a 5% solution; (2) N,N,N',N'-tetramethyl ethylenediamine (TEMED) is added to the solution in step (1), and the volume fraction of TEMED in the suspension is 0.0063%, and the mixture is stirred at room temperature under a nitrogen atmosphere by using a magnetic rotor at a high speed for 1 h; (3) ammonium persulfate (APS) is added to the solution obtained in step (2) while stirring, and the mass fraction of APS in the total mass is 0.1410%, and the mixture is stirred at room temperature for 10 min; (4) the solution obtained in step (3) is dialyzed for 48 h, and the N-isopropyl acrylamide temperature-sensitive hydrogel is obtained after dialysis. Embodiment
[0026] The embodiment of the present application provides a preparation method of a temperature-sensitive hydrogel, which comprises the following steps: (1) N-isopropyl acrylamide is dissolved in deionized water to prepare a 5% solution; (2) N,N,N',N'-tetramethyl ethylenediamine (TEMED) is added to the solution in step (1), and the volume fraction of TEMED in the suspension is 0.0063%, and the mixture is stirred at room temperature under a nitrogen atmosphere by using a magnetic rotor at a high speed for 1 h; (3) ammonium persulfate (APS) is added to the solution obtained in step (2) while stirring, and the mass fraction of APS in the total mass is 0.1410%, and the mixture is stirred at room temperature for 10 min; (4) the solution obtained in step (3) is dialyzed for 48 h, and the N-isopropyl acrylamide temperature-sensitive hydrogel is obtained after dialysis. (5) Carboxymethyl chitosan is dissolved in deionized water under magnetic stirring at room temperature to prepare a 4.5% carboxymethyl chitosan solution; (6) The mixed solution obtained in step (4) is added to the carboxymethyl chitosan solution obtained in step (5) to make it crosslink fully and stable in structure, and the volume ratio of the mixed solution to carboxymethyl chitosan is 2:1, to prepare a temperature-sensitive hydrogel with reversible temperature response. Embodiment
[0027] The embodiment of the present application provides a preparation method of a nanocellulose-based hydrogel, comprising the following steps: (1) 1.0wt% of nanocellulose is extracted from cotton fibers, 2.5g of sodium periodate is added, and the mixture is stirred under magnetic stirring at room temperature for 24h in the dark to prepare an aldehyde group nanocellulose suspension with a concentration of 1%; (2) Carboxymethyl chitosan is dissolved in deionized water under magnetic stirring at room temperature to prepare a 4.5% carboxymethyl chitosan solution; (3) The mixed solution obtained in step (1) is added to the carboxymethyl chitosan solution obtained in step (2) to make it crosslink fully and stable in structure, and the volume ratio of the mixed solution to carboxymethyl chitosan is 2:1, to prepare a nanocellulose-based hydrogel. Embodiment
[0028] The embodiment of the present application provides a preparation method of a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel, comprising the following steps: (1) 1.0wt% of nanocellulose is extracted from cotton fibers, 2.5g of sodium periodate is added, and the mixture is stirred under magnetic stirring at room temperature for 24h in the dark to prepare an aldehyde group nanocellulose suspension with a concentration of 1%; (2) 10ml of the solution obtained in step (1) is taken, 0.5g of N-isopropyl acrylamide and 20μL of N,N,N',N'-tetramethyl ethylenediamine (TEMED) are added to the solution, and the mixture is stirred and dissolved under nitrogen protection at room temperature for 1h; (3) 0.036g of ammonium persulfate (APS) is added to the mixed solution obtained in step (2), and the mixture is stirred and dissolved for 10min; (4) The mixed solution obtained in step (3) is dialyzed in deionized water for 48h, and the water is changed every 4h; (5) Carboxymethyl chitosan is dissolved in deionized water under magnetic stirring at room temperature to prepare a 4.5% carboxymethyl chitosan solution; (6) The mixed solution obtained in step (4) is added to the carboxymethyl chitosan solution obtained in step (5) to make it crosslink fully and stable in structure, and the volume ratio of the mixed solution to carboxymethyl chitosan is 2:1, to prepare a novel medical dressing with reversible temperature response. Embodiment
[0029] The application provides a preparation method of a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel, which comprises the following steps: (1) 1.0 wt% of nanocellulose is extracted from cotton fibers, 2.5 g of sodium periodate is added, and the mixture is magnetically stirred at room temperature in the dark for 24 h to prepare an aldehyde-based nanocellulose suspension with a concentration of 1%; (2) 1 g of N-isopropyl acrylamide and 20 μL of N,N,N',N'-tetramethyl ethylenediamine (TEMED) are added to step (1), and the mixture is fully stirred and dissolved under nitrogen protection at room temperature for 1 h; (3) 0.036 g of ammonium persulfate (APS) is added to the mixed solution obtained in step (2), and the mixture is continuously stirred and dissolved for 10 min; (4) the mixed solution obtained in step (3) is placed in deionized water for dialysis for 48 h, and the water is changed every 4 h; (5) carboxymethyl chitosan is magnetically stirred and dissolved in deionized water at room temperature to prepare a 4.5% carboxymethyl chitosan solution; (6) the mixed solution obtained in step (4) is added to the carboxymethyl chitosan solution obtained in step (5) to make the mixture crosslink and have a stable structure, and the volume ratio of the mixed solution to the carboxymethyl chitosan is 2:1, so that a novel medical dressing with reversible temperature response is prepared. Embodiment
[0030] The application provides a preparation method of a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel, which comprises the following steps: (1) 1.0 wt% of nanocellulose is extracted from cotton fibers, 2.5 g of sodium periodate is added, and the mixture is magnetically stirred at room temperature in the dark for 24 h to prepare an aldehyde-based nanocellulose suspension with a concentration of 1%; (2) 1.5 g of N-isopropyl acrylamide and 20 μL of N,N,N',N'-tetramethyl ethylenediamine (TEMED) are added to step (1), and the mixture is fully stirred and dissolved under nitrogen protection at room temperature for 1 h; (3) 0.036 g of ammonium persulfate (APS) is added to the mixed solution obtained in step (2), and the mixture is continuously stirred and dissolved for 10 min; (4) the mixed solution obtained in step (3) is placed in deionized water for dialysis for 48 h, and the water is changed every 4 h; (5) carboxymethyl chitosan is magnetically stirred and dissolved in deionized water at room temperature to prepare a 4.5% carboxymethyl chitosan solution; (6) The mixed solution obtained in step (4) is added to the carboxymethyl chitosan solution obtained in step (5) to make the cross-linking sufficient and the structure stable, the volume ratio of the mixed solution to the carboxymethyl chitosan is 2:1, and a novel medical dressing with reversible temperature responsiveness is prepared. Embodiment
[0031] The embodiment of the application provides a preparation method of a semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel, which comprises the following steps: (1) 1.0wt% of nanocellulose extracted from cotton fibers is added to 2.5g of sodium periodate, and an aldehyde group nanocellulose suspension with a concentration of 1% is prepared by magnetic stirring at room temperature for 24h in the dark; (2) 2g of N-isopropyl acrylamide and 20μL of N,N,N',N'-tetramethyl ethylenediamine (TEMED) are added to step (1), nitrogen protection is performed, and the solution is fully stirred and dissolved at room temperature for 1h; (3) The mixed solution obtained in step (2) is added to 0.036g of ammonium persulfate (KPS), and the stirring and dissolution are continued for 10min; (4) The mixed solution obtained in step (3) is placed in deionized water for dialysis for 48h, and the water is changed every 4h; (5) Carboxymethyl chitosan is dissolved in deionized water at room temperature by magnetic stirring to prepare a 4.5% carboxymethyl chitosan solution; (6) The mixed solution obtained in step (4) is added to the carboxymethyl chitosan solution obtained in step (5) to make the cross-linking sufficient and the structure stable, the volume ratio of the mixed solution to the carboxymethyl chitosan is 2:1, and a novel medical dressing with reversible temperature responsiveness is prepared.
[0032] Micro-morphology analysis is performed on the hydrogels prepared in Embodiment One to Embodiment Seven: Figure 1 The SEM graph of the cross section of the hydrogel dressing prepared in Embodiment One is shown in the figure. Figure 1 It can be known that the NPI hydrogel without the addition of aldehyde group nanocellulose presents a lamellar structure. Figure 2 The SEM graph of the cross section of the hydrogel dressing prepared in Embodiment Two is shown in the figure. Figure 2 It can be known that the hydrogel with only the addition of carboxymethyl chitosan and N-isopropyl acrylamide presents a little microporous structure, indicating that it has a partial cross-linking structure, but the whole is still loose. Figure 3 The SEM graph of the cross section of the hydrogel dressing prepared in Embodiment Three is shown in the figure. Figure 3 It can be known that the hydrogel prepared from aldehyde group nanocellulose and carboxymethyl chitosan has a three-dimensional porous structure, indicating the gel skeleton effect of DACNF and CMCS, but the arrangement is disorderly and uneven, and cannot provide a free access channel for water molecules and drugs. Figure 4SEM image of the cross-section of the semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel prepared for Example Four, Figure 5 SEM image of the cross-section of the semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel prepared for Example Five, Figure 6 SEM image of the cross-section of the semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel prepared for Example Six, Figures 4-6 It can be seen that the temperature-sensitive hydrogel added with aldehyde-based nanocellulose shows a uniform three-dimensional porous structure, the pore wall is compact and smooth, and the pore diameter is 50-100 μm. This change reflects that the addition of nanocellulose provides a gel skeleton for the hydrogel and provides a channel for water molecules and drugs to enter the interior of the hydrogel; and the pore size structure of the hydrogel is regular and stable, and can effectively load drugs. Figure 7 SEM image of the cross-section of the semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel prepared for Example Seven, Figure 7 It can be seen that the gel network pore size is reduced, the structure is irregular and adhesion and collapse occur, affecting the formation of the pore size.
[0033] Performance analysis of temperature response test of the hydrogels prepared in Examples One to Seven: The phase change behavior of the composite hydrogel depends on the ratio of hydrophilic amide groups to hydrophobic isopropyl groups in the molecular structure. Therefore, the temperature response of Case 3 is not described since it does not have temperature sensitivity. Therefore, under the condition of constant temperature at 35℃, all hydrogels show obvious phase change response. As shown in Figure 8 It can be observed during the experiment that when the hydrogel is transferred from a room temperature environment of 25℃ to 35℃, it quickly becomes white, which is the beginning of dehydration of the gel, and then the solution-gel transition begins. Among them, the hydrogel of Example Seven completes the complete transition from solution to gel state within 300 seconds; while the hydrogel of Example One only appears local shrinkage, and the whole still maintains liquid state, which is due to the non-uniformity of the internal network structure, the water loss in the hydrophobic group rich region is faster, resulting in local rapid shrinkage, thereby showing uneven phenomenon. When the hydrogel is repositioned from a 35℃ environment to a room temperature of 25℃, all six samples recover to solution state within 180 seconds, fully proving the good reversibility of the solution-gel transition process.
[0034] Swelling rate analysis of the hydrogels prepared in Examples One to Seven: After freeze-drying treatment, the hydrogel samples were placed in a buffer solution with a pH of 7.4 to measure their swelling properties, and the results are as follows Figure 9The water gels of Example One and Example Two were dissolved after water absorption and could not be clamped and weighed, so they were not included in the subsequent discussion. The DACNF and CMCS framework is rich in hydrophilic groups, which can bind water molecules through hydrogen bonding, thereby significantly enhancing water absorption. This can be demonstrated by the swelling rate analysis of Example Three, but the structure of the water gel of Example Three collapsed after rapid water absorption, and the gel partially degraded after 8 hours, causing mass loss, which affected the subsequent swelling rate test. The water gels of Example Four to Example Seven all showed rapid water absorption behavior, with a rapid increase in swelling rate within 8 hours. Among them, the swelling rate of Example Four was the highest, reaching 1415.36%, while the swelling rate of Example Seven was the lowest, reaching 626.32%. Higher swelling rate helps to absorb wound exudate and maintain a moist environment for the wound. With the increase of the relative content of NIPAm, the crosslinking density of the gel increases, the molecular chain entanglement is more closely, the three-dimensional network structure tends to be dense, and the pore size decreases (this structural change can also be verified from the SEM images), ultimately leading to a gradual decrease in the swelling rate.
[0035] Antibacterial performance analysis of the water gels prepared in Example One to Example Seven: To evaluate the antibacterial performance of the water gels, Staphylococcus aureus (representative of Gram-positive bacteria) and Escherichia coli (representative of Gram-negative bacteria) were selected, and the antibacterial activity was evaluated by the inhibition rate. The agar plate culture results and inhibition rates of different water gels are shown in Figure 10 As can be seen from the figure, the NPI water gel without adding nanocellulose has weak inhibition effect on the two bacteria; after the introduction of nanocellulose, the number of bacteria in the plate of the water gels of Example Four to Example Seven series is significantly reduced with the increase of the relative concentration of nanocellulose, indicating that nanocellulose can effectively enhance the antibacterial performance of the water gel. Among them, the highest inhibition rate for Staphylococcus aureus is 99.95%, and the highest inhibition rate for Escherichia coli is 99.95%. This result provides experimental basis for the application of such temperature-responsive water gels in medical wound dressings.
[0036] Although embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made therein without departing from the principles and spirit of the application, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel, characterized by: The hydrogel is prepared by physical cross-linking and chemical cross-linking of water, aldehyde-modified nanocellulose, water-soluble polysaccharide derivatives and temperature-sensitive monomers; The aldehyde-modified nanocellulose is prepared from nanocellulose extracted from cotton and hemp plants by sodium periodate aldehyde modification treatment; The water-soluble polysaccharide derivative is one or more of carboxymethyl chitosan or quaternary ammonium salt chitosan; The temperature-sensitive monomer is one or more of N-isopropyl acrylamide or poloxamer; The aldehyde-modified nanocellulose and the temperature-sensitive monomer are covalently connected by free radicals to form a first network; The aldehyde-modified nanocellulose and the water-soluble polysaccharide derivative form an imine bond to form a second network.
2. The semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel according to claim 1, characterized in that: The nanocellulose extracted from cotton and hemp plants is one or both of nanocellulose crystals and nanocellulose fibers.
3. The semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel according to claim 1, characterized in that: The water-soluble polysaccharide derivative is carboxymethyl chitosan.
4. The method for preparing a semi-interpenetrating network structure thermosensitive nanocellulose-based hydrogel according to claim 1, characterized in that: The method comprises the following steps: Step one: mix the nanocellulose solution with the sodium periodate solution, adjust the pH of the mixed system to 4-5 at room temperature 20-25℃ using PBS, and stir at 100-200r / min for 12-24h to obtain a first solution; wherein the weight ratio of sodium periodate to nanocellulose is 1.19-3.66:1; Step two: add ethylene glycol to the first solution, the molar ratio of ethylene glycol to sodium periodate in step one is 1:1, stir at 20-25℃ and 100-200r / min for 1-2h to obtain a second solution; Step three: place the second solution in a dialysis bag with a molecular weight cut-off of 4500Da, dialyze with deionized water for 3-5 days, freeze-dry the solution after dialysis for 3 days, add deionized water to the dried product and ultrasonic disperse for 24h to obtain a third solution with a mass fraction of 1.0wt%; Step four: add the temperature-sensitive monomer and the first initiator to the third solution, stir at 20-25℃ and 100-200r / min for 1-2h under nitrogen protection to obtain a fourth solution; Step five: add the second initiator to the fourth solution, stir at 20-25℃ and 100-200r / min for 10-30min to obtain a fifth solution; Step six: place the fifth solution in a dialysis bag with a molecular weight cut-off of 4500Da, dialyze with deionized water for 1-3 days to obtain a sixth solution; Step seven: add the water-soluble polysaccharide derivative to deionized water, the amount ratio of the water-soluble polysaccharide derivative to deionized water is 2.25g:50ml, stir at 20-60℃ and 100-200r / min for 12-24h to obtain a seventh solution; Step eight: add the sixth solution to the seventh solution, the volume ratio of the seventh solution to the sixth solution is 1:1-2, stir at 10-25℃ and 10-100r / min for 5-10min to complete the physical cross-linking and chemical cross-linking to obtain the semi-interpenetrating network structure temperature-sensitive nanocellulose-based hydrogel.
5. The method for preparing a semi-interpenetrating network structure thermosensitive nanocellulose-based hydrogel according to claim 4, characterized in that: In step one, the nanocellulose is nanocellulose fiber, the stirring reaction temperature is 25℃, and the stirring reaction time is 24h.
6. The method for preparing a semi-interpenetrating network structure thermosensitive nanocellulose-based hydrogel according to claim 4, characterized in that: In step four, the temperature-sensitive monomer is N-isopropyl acrylamide, the first initiator is N,N,N',N'-tetramethyl ethylenediamine, the reaction temperature is 25℃, and the reaction time is 1h.
7. The method for preparing a semi-interpenetrating network structure thermosensitive nanocellulose-based hydrogel according to claim 4, characterized in that: In step five, the second initiator is ammonium persulfate, the reaction temperature is 25℃, and the reaction time is 10min.
8. The method for preparing a semi-interpenetrating network structure thermosensitive nanocellulose-based hydrogel according to claim 4, characterized in that: In step seven, the water-soluble polysaccharide derivative is carboxymethyl chitosan, the stirring temperature is 25℃, and the stirring time is 24h.
9. The method for preparing a semi-interpenetrating network structure thermosensitive nanocellulose-based hydrogel according to claim 4, characterized in that: In step eight, the stirring temperature is 15℃, and the stirring time is 5min.
10. The use of the semi-IPN structure temperature-sensitive nanocellulose-based hydrogel prepared according to any one of claims 4-9 in wound dressings.
Citation Information
Patent Citations
Wound dressing based on poly (N-isopropylacrylamide) hydrogel microspheres
CN222075415U